Vocational training costs and economic benefits: exploring the interactions - Samoliuk, Natalia; Bilan, Yuriy; Mishchuk, Halyna (Journal of Business Economics and Management, 2021)
The aim of the article is to study the relationship between vocational training costs and economic benefits at different levels of economic relations. In the structure of labour costs in the EU, there was the highest share of vocational training costs in Ireland (2.79%), Great Britain (2.53%), France (1.51%), which is reflected in the economic success of these countries. A comparison with Ukraine, which has European integration intentions, confirms that the underestimated role of investing in lifelong learning has relevant links to economic performance. This study at the enterprise level (based on the survey of 356 employees) found that higher costs of vocational training are a sign of profitable enterprises. At the same time, employees’ interest in short-term training programs is higher, which they obviously assess from the standpoint of higher personal economic benefits in the short term. At the same time, the analysis performed by means of the Fechner correlation coefficient confirms the existence of a positive impact of vocational training costs on changes in the main macroeconomic benefits indicator – GDP per capita. This allows drawing conclusions about the need to develop professional training programs for staff as one of the drivers of macroeconomic development.